Extraction of biosurfactant from pseudomonas aeruginosa inhabiting oil-spilled soils - Alex Yagoo; Jelin Vilvest (SpringerOpen, 2023)
Abstract Background Screening for biosurfactant-producing microbes involves the process of sampling and isolating bacteria from various environmental sources. Hydrocarbon-contaminated locations are considered ideal sources for isolating bacteria that produce biosurfactants. This is because these microbes have adapted to living in oil-contaminated environments and have developed mechanisms to produce biosurfactants as a means of survival. Therefore, screening microbes from such locations increases the likelihood of finding bacteria capable of producing biosurfactants. Results This investigation aimed to isolate bisurfactant-producing bacteria from oil-contaminated soil samples, with a particular focus on Pseudomonas aeruginosa. Out of the 10 samples collected, four were confirmed to be P. aeruginosa, and all strains showed positive results for antagonistic, hemolytic, and emulsification tests. The strains were effective against B. subtilis, S. aureus, and E. coli but less effective against A. hydrophila. The PS10 strain exhibited the highest emulsification index, while PS08 showed the lowest. Based on microscopic and biochemical examination, P. aeruginosa was identified as the most effective isolate. Conclusion These findings highlight the potential of P. aeruginosa as a biosurfactant producer for industrial and environmental applications. However, further studies are needed to fully understand the biosurfactant production potential of these strains and to optimize the conditions for biosurfactant production.